Reexamining the Relationship between Output Gap and Risk Premiums in Aseans - Dhakan, Darshan Vinod Odhavji (2014)
This study examines if there the link between the output gap and stock risk premiums of the ASEAN 5 countries. This study based on the business cycle theory which the pattern of expansions contractions and recovery. Stock markets and output have in the presence been seen to move in the same general direction due to which we hypothesize that movements in macro economic variables cause movements in stock prices. We find there is a link between stock prices and industrial production for all the countries except Indonesia and Philippines. Findings also show that there is a link between the output gap and stock premium for Indonesia, Malaysia and Singapore only. Philippine is the only country that does not show a link between a production-based macro economic variable. We find that the output gap is a good predictor of stock excess returns for Malaysia and Thailand but is unable to given successful out of sample results. Results highlight the linkages between economic activity and stock prices which policy makers and investors should take note of to anticipate movements in the stock markets or economic activity.